Potencialidades da justiça restaurativa para a instauração de uma nova lógica na custódia psiquiátrico-penal : reflexões a partir de pesquisa empírica na Unidade de Custódia Psiquiátrica de Sergipe - Paixão, Gabriela Silva (2023)
The persistence of Forensic Mental Health Setting and its treatment in the Criminal Justice system defies the anti-asylum movement, as well as the psychiatric restoration that was brought up decades ago in Brazil. Redirecting therapeutic practice to a communal environment and banning the interdiction of patients in asylums are rules that do not reach those subjected to custody through security measures. The line of thought that views criminal offense as an expression of risk justifies this segregation in a dubious space, which unifies a prison and a hospital. Therefore, criminal response comes through torment, which is inherent to the retributive model established by modern criminal rationality. With the distress that this scenario arises, the objective is to investigate the potential of Restorative Justice to setting up a new logic of conflict management in psychiatric custody. The questions are directed towards the possibility of dialogue between restoration's principles and values and the specific field of psychiatric suffering of those who are in conflict with the legal system. As such, the research will be both theoretical and empirical, through bibliographic review and document analysis, as well as active observation in Sergipe's Forensic Mental Health Setting. In conclusion, through the review of foreigner papers, we acknowledged that it is possible to apply restorative practices in forensic mental unities, such as contact between victm and offender and circles of support and accountability, regarding the particularities that involves this field.